EDUCATION: COLONIZATION OR THE PEDAGOGY OF SUBJUGATION (Heritage, 2025)
Education represents a crucial developmental resource for any society, encompassing both its potential and prosperity. It is also a determinant of its success, an agent of socialization, and a means for learning values.  It constitutes a key element of class structure and the stratification pyramid, and serves as an instrument for their maintenance. In order to maintain societal and state order, education plays a key role in institutionalizing value orientations, cementing cultural cohesion, and differentiating social roles, and frames occupations as vocations, responsibilities, obligations, and duties. Consequently, the most effective means of undermining a nation and its state is through the destruction of its educational and upbringing systems. This is achieved through mechanisms of control, surveillance, and repression, directing people towards advertisements, media, and social networks, marketing, and paternalism, all devoid of spirit, imagination, or spirituality. In this context, education within the globalized periphery has become an instrument of colonization and a tool of pedagogy aimed at subjugation and enslavement. It relegates individuals to metaphorical straitjackets, masked as neutral transitions, while enabling the rise of a volatile, gangster-style political capitalism with no alternatives. A system that values means over ends, utility over goods, earnings and profit over intellectual and human values, and relies increasingly on robots and artificial intelligence. In the near future, these technological advancements will displace many diploma-holders from the labor market. This is a new code and permit for inequality, the triumph of poverty, and the establishment of global totalitarianism, in which the classical form will become a mere swan song. This issue necessitates a reimagined discourse and a redefined understanding both theoretical and epistemological, as well as practical and educational. That is how all progress begins.
Keywords: education, colonization, global totalitarianism, time, progress.